The effect of antibacterial and non-antibacterial compounds alone or associated with antifugals upon fungi - Azevedo, Maria M.; Teixeira-Santos, Rita; Silva, Ana P.; Cruz, Luisa; Ricardo, Elisabete; Pina-Vaz, Cidália; Rodrigues, Acácio G. (Frontiers in Microbiology, 2015)
During the last 30 years the incidence of fungal infections has increased dramatically. While the antifungal therapeutic options available are somewhat reduced, most pathogenic microorganisms have an incredible capacity to mutate and acquire resistance. In addition, multiple drugs are often required concomitantly to manage clinically complex disorders. The combination of antibiotics or other compounds with antifungal drugs, simultaneously or sequentially, is commonly adopted in clinical practice, although without a full knowledge of the consequences. Thus, the role of combined therapy and the effect of antibiotics upon fungal growth promotion need to be critically evaluated and understood in order to avoid undesirable drug interactions. With this review we intend discuss the studies that report about antibiotics inhibiting fungal growth, as well as studies describing the synergistic effect of the combined therapy, i.e., associations between antibiotics or other compounds with antifungal drugs. Alternative therapeutic protocols for fungal disease could be designed, taking advantage of such drug combinations. Critical revision of previously published data is crucial in order to define future research strategies.